Associations between age, respiratory comorbidities, and dysphagia in infants with down syndrome. Issue 11 (12th August 2019) - Jackson, Arwen; Maybee, Jennifer; Wolter‐Warmerdam, Kristine; DeBoer, Emily; Hickey, Francis
Abstract: Objectives: Children with Down syndrome (DS) have a high risk of dysphagia and the pediatric pulmonologist may be involved in diagnosis and management. The objective of this study is to evaluate the associations between age, dysphagia, and medical comorbidities in young children with DS. We hypothesized that swallow study findings are more likely to change in younger infants and that medical comorbidities may be associated with dysphagia. Study design: Results of videofluoroscopic swallow studies (VFSS) and fiberoptic endoscopic evaluation of swallowing (FEES) from 2010 to 2016 were collected retrospectively in children with DS with initial swallow study at less than 12 months of age. Results were analyzed for findings and change based on age at initial study, reason for referral, and medical comorbidities. Results: One hundred eleven infants with 247 VFSS and 14 FEES were included. Deep laryngeal penetration and/or aspiration were found in 31.9% of infants less than 6 months and 51.3% of infants 6 to 12 months. Children with initial swallow study performed at greater than or equal to 6 months of age were more likely (80.0%) to have unchanged findings on follow‐up study compared to children imaged at less than 6 months (35.3%). Laryngomalacia, pulmonary hypertension, pneumonia, and congenital cardiac disease were associated with dysphagia. Conclusion: We confirmed that dysphagia is common in infants with DS and comorbidities and provided preliminary evidence that swallow study findings may be more likely to change in children tested under 6 months of age. Providers should consider that results for instrumental swallow studies may change, particularly if the test was completed on a young infant.